Carbon nitride quantum dot with surface and inner core dual design and preparation method of carbon nitride quantum dot

By doping boron and phosphorus elements into the core of carbon nitride quantum dots and modifying polyacrylic acid on the surface, the problem of insufficient physical and chemical performance of existing carbon nitride quantum dots has been solved, and performance improvement and application expansion has been achieved, especially suitable for water-based lubricating additives.

CN119529307APending Publication Date: 2025-02-28PANZHIHUA UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411713483.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing carbon nitride quantum dots have limitations in physical and chemical performance and application fields, especially the single type and insufficient performance improvement, which limits its further development.

Method used

Using a dual surface and core design method, carbon nitride quantum dots with uniform size distribution and good hydrophilicity are formed by doping boron and phosphorus elements into the core of carbon nitride quantum dots and covalent modification of polyacrylic acid on the surface.

Benefits of technology

It has achieved physical and chemical performance improvement of carbon nitride quantum dots, has good dispersion and lubricity, and is suitable for water-based lubricating additives, which significantly improves anti-wear and friction reduction performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529307A_ABST
    Figure CN119529307A_ABST
Patent Text Reader

Abstract

The invention relates to a carbon nitride quantum dot with surface and core dual design and a preparation method thereof, and belongs to the technical field of nano materials. In order to achieve the first purpose, the carbon nitride quantum dot with the surface and inner core dual design comprises at least one of polyacrylic acid with the average particle size of 3-10 nm, the inner core co-doped with boron and phosphorus elements and the surface covalently modified with the average molecular weight of 2000-5000. The preparation method of the carbon nitride quantum dot with the double design of the surface structure and the core structure is simple, easy to operate and wide in large-scale production prospect. While the carbon nitride quantum dots are prepared, boron and phosphorus elements are doped in the cores, polyacrylic acid functional groups are covalently modified on the surfaces of the carbon nitride quantum dots, and the obtained carbon nitride quantum dots with double design of surface and core structures are uniform in size distribution and have good hydrophilicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbon nitride quantum dot with dual surface and core design and a preparation method thereof, belonging to the technical field of nanomaterials. Background Art

[0002] Carbon nitride quantum dots are a new type of nanomaterial, which has a structure similar to graphene quantum dots, has the structural characteristics of graphene and carbon nitride, and usually exhibits excellent optical, electrical and catalytic properties. Carbon nitride quantum dots have many advantages such as simple preparation method, excellent optical properties, green and environmental protection, and have potential applications in sensing, nanomedicine, catalysis, lubrication and other fields. However, the current carbon nitride quantum dots also have defects such as single type and physical and chemical properties need to be improved, which greatly limits their further development. Studies have shown that carbon nitride quantum dots have the characteristics of strong structural and compositional designability and easy functionalization, so their physical and chemical properties, functions and uses can be artificially controlled. Chemical functionalization is an effective way to modify and improve the physical and chemical properties of carbon nitride quantum dots. Chemical functionalization can significantly expand the application range of carbon nitride quantum dots. At present, researchers mostly use single functionalization methods to improve the physical and chemical properties of carbon nitride quantum dots, such as heteroatom doping, structural modification, precursor functionalization, copolymerization, surface grafting, etc. The single functionalization method introduces chemical components such as organic small molecules, polymers, heteroatoms, surfactants, etc. into the core or surface of carbon nitride quantum dots by covalent bonds or non-covalent bonds, thereby giving them more excellent physical and chemical properties.

[0003] The dual functionalization method is expected to further improve the physical and chemical properties of carbon nitride quantum dots, thereby further broadening their application areas and application value. The dual functionalization method is to functionalize the core and surface of carbon nitride quantum dots at the same time, such as doping the core structure of carbon nitride quantum dots with heteroatoms and metal atoms, and at the same time functionalizing the surface of carbon nitride quantum dots with organic small molecules, polymers, etc., so that the developed and designed carbon nitride quantum dot materials have more practical application value. However, there are few reports on the research of carbon nitride quantum dots involving dual design of surface and core structure.

[0004] CN105670620A discloses a method for preparing doped carbon nitride fluorescent quantum dots. The present invention uses melamine and compounds corresponding to doping atoms as raw materials. When melamine molecules are calcined to form a carbon nitride structure, doping atoms enter the carbon nitride structure through chemical reactions to form a doped carbon nitride bulk material. The bulk material is ultrasonically crushed in an alcohol solvent to prepare quantum-sized, uniformly-sized doped carbon nitride quantum dots. The dried quantum dots have good water solubility, good dispersibility, and high fluorescence quantum yield. This method can prepare doped carbon nitride quantum dots in batches, and the synthesis method is simple and has good repeatability. The synthesized quantum dots have broad application prospects in the fields of fluorescence detection, light-emitting devices, and biomarkers. However, it is a single functionalization method to improve the physicochemical properties of carbon nitride quantum dots. Summary of the invention

[0005] The first object of the present invention is to provide a novel carbon nitride quantum dot with dual surface and core designs.

[0006] To achieve the first object of the present invention, the carbon nitride quantum dots with dual surface and core designs have an average particle size of 3 to 10 nm, the core is co-doped with boron and phosphorus elements, and the surface is covalently modified with polyacrylic acid with an average molecular weight of 2000 to 5000.

[0007] In a specific embodiment, the method for preparing the carbon nitride quantum dots with dual surface and core designs comprises the following steps:

[0008] a. Mix urea, diammonium hydrogen phosphate and boron trioxide and grind them for 5 to 15 minutes, then calcine them at 400 to 600°C for 3 to 6 hours, and grind the calcined product into powder to obtain boron and phosphorus co-doped carbon nitride;

[0009] b. mixing the carbon nitride described in step a with a 4-6 mol / L solution, stirring and reacting at 100-140° C. for 16-28 h, cooling to room temperature, washing, solid-liquid separation, freeze-drying the solid, and grinding the resulting product into a powder to obtain an intermediate;

[0010] c. Mix the intermediate, polyacrylic acid and ionized water in step b, and ultrasonically treat for 15 to 30 min to obtain a dispersion, and hydrothermally react the dispersion at 160 to 240 ° C for 16 to 28 h to obtain a milky white dispersion;

[0011] d. The milky white dispersion in step c is centrifuged at 7000-10000 rpm for 5-20 min to obtain a supernatant, and the supernatant is freeze-dried to obtain carbon nitride quantum dots with dual surface and core designs.

[0012] In a specific embodiment, the mass ratio of urea, diammonium hydrogen phosphate and boron trioxide in step a is 4:0.5-1.5:0.5-1.5.

[0013] Preferably, the molar mass ratio of urea, diammonium hydrogen phosphate and boron trioxide in step a is 4:1:1.

[0014] In a specific embodiment, the mass volume ratio of the intermediate and polyacrylic acid in step b is 1 g:10-40 mL.

[0015] Preferably, the mass volume ratio of the intermediate and polyacrylic acid in step b is 1 g:20 mL.

[0016] In a specific embodiment, the mass volume ratio of the carbon nitride and nitric acid solution in step b is 1g:20-40mL.

[0017] In a specific embodiment, the hydrothermal reaction time in step c is 24 hours.

[0018] The second object of the present invention is to provide a method for preparing the above-mentioned carbon nitride quantum dots with dual surface and core designs.

[0019] To achieve the second object of the present invention, the method comprises the following steps:

[0020] a. Mix urea, diammonium hydrogen phosphate and boron trioxide and grind them for 5 to 15 minutes, then calcine them at 400 to 600°C for 3 to 6 hours, and grind the calcined product into powder to obtain boron and phosphorus co-doped carbon nitride;

[0021] b. Mix the carbon nitride described in step a with a 4 to 6 mol / L nitric acid solution, stir and react at 100 to 140 ° C for 16 to 28 hours, cool to room temperature, wash, separate the solid from the liquid, freeze-dry and grind the solid to obtain an intermediate;

[0022] c. Mix the intermediate, polyacrylic acid and ionized water in step b, and ultrasonically treat for 15 to 30 min to obtain a dispersion, and hydrothermally react the dispersion at 160 to 240 ° C for 16 to 28 h to obtain a milky white dispersion;

[0023] d. The milky white dispersion in step c is centrifuged at 7000-10000 rpm for 5-20 min to obtain a supernatant, and the supernatant is freeze-dried to obtain carbon nitride quantum dots with dual surface and core designs.

[0024] In a specific embodiment, the molar mass ratio of urea, diammonium hydrogen phosphate and boron trioxide in step a is 4:0.5-1.5:0.5-1.5.

[0025] Preferably, the molar mass ratio of urea, diammonium hydrogen phosphate and boron trioxide in step a is 4:1:1.

[0026] In a specific embodiment, the mass volume ratio of the intermediate and polyacrylic acid in step b is 1 g: 10-40 mL;

[0027] Preferably, the mass volume ratio of the intermediate and polyacrylic acid in step b is 1 g:20 mL; the mass volume ratio of the carbon nitride and nitric acid solution in step b is preferably 1 g:20-40 mL.

[0028] In a specific embodiment, the hydrothermal reaction time in step c is 24 hours.

[0029] Beneficial effects:

[0030] (1) The preparation method of carbon nitride quantum dots with dual surface and core structure designs of the present invention is simple and easy to operate, and has broad prospects for large-scale production.

[0031] (2) The present invention dopes boron and phosphorus into the core of carbon nitride quantum dots while preparing them, and covalently modifies the surface with polyacrylic acid functional groups. The obtained carbon nitride quantum dots have a uniform size distribution and good hydrophilicity, and are used as water-based lubricating additives with good lubrication properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The structural formula of carbon nitride quantum dots with dual surface and core structures is provided, wherein M is boron and phosphorus elements co-doped in the core of the carbon nitride quantum dots; and R is polyacrylic acid with an average molecular weight of 2000 to 5000 covalently modified on the surface of the carbon nitride quantum dots through amide bonds.

[0033] Figure 2 This is an electron microscope image of the carbon nitride quantum dots with dual surface and core designs prepared in Example 1.

[0034] Figure 3 This is the infrared spectrum detection result of the carbon nitride quantum dots with dual surface and core designs prepared in Example 1. DETAILED DESCRIPTION

[0035] In order to achieve the first object of the present invention, the carbon nitride quantum dots with dual surface and core designs include an average particle size of 3 to 10 nm, a core co-doped with boron and phosphorus elements, and a surface covalently modified with polyacrylic acid with an average molecular weight of 2000 to 5000, and a structural formula as shown below: Figure 1 shown.

[0036] In a specific embodiment, the method for preparing the carbon nitride quantum dots with dual surface and core designs comprises the following steps:

[0037] a. Mix urea, diammonium hydrogen phosphate and boron trioxide and grind them for 5 to 15 minutes, then calcine them at 400 to 600°C for 3 to 6 hours, and grind the calcined product into powder to obtain boron and phosphorus co-doped carbon nitride;

[0038] b. mixing the carbon nitride described in step a with a 4-6 mol / L solution, stirring and reacting at 100-140° C. for 16-28 h, cooling to room temperature, washing, solid-liquid separation, freeze-drying the solid, and grinding the resulting product into a powder to obtain an intermediate;

[0039] c. Mix the intermediate, polyacrylic acid and ionized water in step b, and ultrasonically treat for 15 to 30 min to obtain a dispersion, and hydrothermally react the dispersion at 160 to 240 ° C for 16 to 28 h to obtain a milky white dispersion;

[0040] d. The milky white dispersion in step c is centrifuged at 7000-10000 rpm for 5-20 min to obtain a supernatant, and the supernatant is freeze-dried to obtain carbon nitride quantum dots with dual surface and core designs.

[0041] In a specific embodiment, the mass ratio of urea, diammonium hydrogen phosphate and boron trioxide in step a is 4:0.5-1.5:0.5-1.5.

[0042] Preferably, the molar mass ratio of urea, diammonium hydrogen phosphate and boron trioxide in step a is 4:1:1.

[0043] In a specific embodiment, the mass volume ratio of the intermediate and polyacrylic acid in step b is 1 g:10-40 mL.

[0044] Preferably, the mass volume ratio of the intermediate and polyacrylic acid in step b is 1 g:20 mL.

[0045] In a specific embodiment, the mass volume ratio of the carbon nitride and nitric acid solution in step b is 1g:20-40mL.

[0046] In a specific embodiment, the hydrothermal reaction time in step c is 24 hours.

[0047] The second object of the present invention is to provide a method for preparing the above-mentioned carbon nitride quantum dots with dual surface and core designs.

[0048] To achieve the second object of the present invention, the method comprises the following steps:

[0049] a. Mix urea, diammonium hydrogen phosphate and boron trioxide and grind them for 5 to 15 minutes, then calcine them at 400 to 600°C for 3 to 6 hours, and grind the calcined product into powder to obtain boron and phosphorus co-doped carbon nitride;

[0050] b. Mix the carbon nitride described in step a with a 4 to 6 mol / L nitric acid solution, stir and react at 100 to 140 ° C for 16 to 28 hours, cool to room temperature, wash, separate the solid from the liquid, freeze-dry and grind the solid to obtain an intermediate;

[0051] c. Mix the intermediate, polyacrylic acid and ionized water in step b, and ultrasonically treat for 15 to 30 min to obtain a dispersion, and hydrothermally react the dispersion at 160 to 240 ° C for 16 to 28 h to obtain a milky white dispersion;

[0052] d. The milky white dispersion in step c is centrifuged at 7000-10000 rpm for 5-20 min to obtain a supernatant, and the supernatant is freeze-dried to obtain carbon nitride quantum dots with dual surface and core designs.

[0053] In a specific embodiment, the molar mass ratio of urea, diammonium hydrogen phosphate and boron trioxide in step a is 4:0.5-1.5:0.5-1.5.

[0054] Preferably, the molar mass ratio of urea, diammonium hydrogen phosphate and boron trioxide in step a is 4:1:1.

[0055] In a specific embodiment, the mass volume ratio of the intermediate and polyacrylic acid in step b is 1 g: 10-40 mL;

[0056] Preferably, the mass volume ratio of the intermediate and polyacrylic acid in step b is 1 g:20 mL; the mass volume ratio of the carbon nitride and nitric acid solution in step b is preferably 1 g:20-40 mL.

[0057] In a specific embodiment, the hydrothermal reaction time in step c is 24 hours.

[0058] The specific implementation modes of the present invention are further described below in conjunction with embodiments, but the present invention is not limited to the scope of the embodiments.

[0059] Example 1

[0060] The preparation method of multi-metal co-doped carbon quantum dot-based polyethylene glycol nano-additive specifically comprises the following steps:

[0061] (1) Weighing 20 g of urea, 5 g of diammonium hydrogen phosphate and 5 g of boron trioxide, mixing them evenly and grinding them in a mortar; then transferring them to a crucible, moving the crucible to a muffle furnace, and calcining them at 550° C. for 4 h; grinding the calcined product into powder to obtain boron and phosphorus co-doped carbon nitride;

[0062] (2) Weigh 2.0 g of the boron and phosphorus co-doped carbon nitride in step (1) and place it in 50 mL of 6 mol / L nitric acid solution, stir and react for 24 h in an oil bath at 120° C., and equip it with a reflux condenser. After the solution is cooled, wash and filter repeatedly until the washing liquid is neutral, take out the solid product and freeze-dry it, grind the dried solid product to obtain an intermediate;

[0063] (3) Weighing 0.5 g of the intermediate obtained in step (2) and 10 mL of polyacrylic acid (average molecular weight of 2000) were added to 50 mL of deionized water, and ultrasonically treated for 30 min to obtain a dispersion, and the dispersion was transferred to a reactor and hydrothermally reacted at 180° C. for 24 h to obtain a milky white dispersion;

[0064] (4) The dispersion in step (3) was transferred to a centrifuge tube and centrifuged at 10,000 rpm for 10 min to obtain a supernatant; then, the supernatant was freeze-dried to obtain carbon nitride quantum dots with dual surface and core designs.

[0065] like Figure 2 As shown, the carbon nitride quantum dots with dual surface and core designs prepared above have a spherical structure, uniform size distribution, and an average particle size of about 5.7 nm.

[0066] like Figure 3 As shown, the surface of the carbon nitride quantum dots with dual surface and core designs prepared above is covalently modified with a large number of polyacrylic acid groups (average molecular weight of 2000), resulting in the carbon nitride quantum dots having good dispersibility in water.

[0067] Embodiment 2-10

[0068] Similarly, urea, diammonium hydrogen phosphate and boron trioxide were selected as raw materials, polyacrylic acid was used as a functionalizing agent, and the ratio of raw materials and functionalizing agents, the molecular weight of polyacrylic acid, the hydrothermal reaction time and other parameters were adjusted. The corresponding experimental scheme was referred to Example 1, and Examples 2-10 all prepared carbon nitride quantum dots with dual surface and core designs. The corresponding experimental parameters and experimental results are shown in Table 1:

[0069] Table 1 Experimental parameters and experimental results of Examples 2-10

[0070]

[0071]

[0072] The size distribution of the carbon nitride quantum dots with dual surface and core designs prepared in Examples 2 to 10 is uniform, but the amount of boron and phosphorus elements doped in the core is inconsistent, and the amount and molecular weight of the polyacrylic acid modified on the surface are also inconsistent, resulting in differences in their average particle sizes. The carbon nitride quantum dots with dual surface and core designs can be dispersed stably in water for a long time and show good hydrophilicity, so they can be used as water-based nano-lubricating additives.

[0073] Comparative Examples 1-6

[0074] The experimental scheme refers to Example 1, and the experimental parameters and experimental results of Comparative Examples 1-6 are shown in Table 2:

[0075] Table 2 Experimental parameters and experimental results of comparative examples 1-6

[0076] Comparative Example 1 2 3 4 5 6 Urea(g) 20 20 20 20 20 20 Diammonium hydrogen phosphate (g) 5 5 5 0 5 5 Boron trioxide(g) 0.5 5 5 0 0 5 Polyacrylic acid: average molecular weight 2000 (mL) 10 10 10 10 10 0 Polyacrylic acid: average molecular weight 3000 (mL) 0 0 0 0 0 0 Polyacrylic acid: average molecular weight 4000 (mL) 0 0 0 0 0 0 Polyacrylic acid: average molecular weight 5000 (mL) 0 0 0 0 0 0 Hydrothermal reaction temperature (℃) 180 120 300 180 180 180 Hydrothermal reaction time (h) 24 24 24 24 24 24 Average particle size of carbon nitride quantum dots (nm) 5.2 23.5 0 3.9 4.7 5.0

[0077] The carbon nitride quantum dots prepared in Comparative Example 1 do not contain boron element.

[0078] The particle size of the carbon nitride quantum dots prepared in Comparative Example 2 is much larger than 10 nm, while the particle size of quantum dots is required to be less than 10 nm, so it does not belong to the category of quantum dots; Comparative Example 3 does not have carbon nitride quantum dots. Comparative Example 4 has only polyacrylic acid modified on the surface, without boron and phosphorus doping; Comparative Example 5 has only phosphorus doped in the core of the carbon nitride quantum dots, and the surface is modified with polyacrylic acid; Comparative Example 6 has boron and phosphorus co-doped in the core of the carbon nitride quantum dots, and the surface is not modified with polyacrylic acid.

[0079] The carbon nitride quantum dots prepared in Example 1, Comparative Example 1, Comparative Example 4, Comparative Example 5, and Comparative Example 6 are used as water-based lubricant additives. The water-based lubricant is a common 2.0wt% triethanolamine aqueous solution, and 1.0wt% of carbon nitride quantum dots are added. The carbon nitride quantum dots in Example 1 can improve the anti-wear performance of the water-based lubricant by 87.1% and the friction reduction performance by 52.1% at most; the carbon nitride quantum dots prepared in Comparative Example 1 are used as water-based lubricant additives to improve the anti-wear and friction reduction performance by 68.5% and 44.6%, respectively; the carbon nitride quantum dots prepared in Comparative Example 4 are used as water-based lubricant additives to improve the The anti-wear and friction reduction properties are improved by 52.1% and 37.9% respectively; the carbon nitride quantum dots prepared in comparative example 5 are used as water-based lubricating additives to improve their anti-wear and friction reduction properties by 74.2% and 46.6% respectively; the carbon nitride quantum dots prepared in comparative example 6 are used as water-based lubricating additives to improve their anti-wear and friction reduction properties by 38.8% and 25.2% respectively; it can be seen that the tribological properties of the carbon nitride quantum dots with dual surface and core designs prepared in Example 1 as water-based lubricating additives are significantly better than those of the carbon nitride quantum dots prepared in comparative examples 1, 4, 5 and 6, and the application effect is better.

Claims

1. Carbon nitride quantum dots with dual surface and core designs, characterized in that: The carbon nitride quantum dots with dual surface and core designs have an average particle size of 3 to 10 nm, the core is co-doped with boron and phosphorus elements, and the surface is covalently modified with at least one polyacrylic acid with an average molecular weight of 2000 to 5000 through amide bonds.

2. The carbon nitride quantum dots with dual surface and core designs according to claim 1, characterized in that: The method for preparing carbon nitride quantum dots with dual surface and core designs comprises the following steps: a. Mix urea, diammonium hydrogen phosphate and boron trioxide and grind them for 5 to 15 minutes, then calcine them at 400 to 600°C for 3 to 6 hours, and grind the calcined product into powder to obtain boron and phosphorus co-doped carbon nitride; b. mixing the carbon nitride described in step a with a 4-6 mol / L solution, stirring and reacting at 100-140° C. for 16-28 h, cooling to room temperature, washing, solid-liquid separation, freeze-drying the solid, and grinding the resulting product into a powder to obtain an intermediate; c. Mix the intermediate, polyacrylic acid and ionized water in step b, and ultrasonically treat for 15 to 30 min to obtain a dispersion, and hydrothermally react the dispersion at 160 to 240 ° C for 16 to 28 h to obtain a milky white dispersion; d. The milky white dispersion in step c is centrifuged at 7000-10000 rpm for 5-20 min to obtain a supernatant, and the supernatant is freeze-dried to obtain carbon nitride quantum dots with dual surface and core designs.

3. The carbon nitride quantum dots with dual surface and core designs according to claim 2, characterized in that: The mass ratio of urea, diammonium hydrogen phosphate and boron trioxide in step a is 4:0.5-1.5:0.5-1.5; preferably 4:1:

1.

4. The carbon nitride quantum dots with dual surface and core designs according to claim 2, characterized in that: The mass volume ratio of the intermediate and polyacrylic acid in step b is 1 g:10-40 mL, preferably 1 g:20 mL.

5. The carbon nitride quantum dots with dual surface and core designs according to claim 2, characterized in that: The mass volume ratio of the carbon nitride and nitric acid solution in step b is 1g:20-40mL.

6. The carbon nitride quantum dots with dual surface and core designs according to claim 2, characterized in that: The hydrothermal reaction time in step c is 24 h.

7. The method for preparing carbon nitride quantum dots with dual surface and core designs according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: a. Mix urea, diammonium hydrogen phosphate and boron trioxide and grind them for 5 to 15 minutes, then calcine them at 400 to 600°C for 3 to 6 hours, and grind the calcined product into powder to obtain boron and phosphorus co-doped carbon nitride; b. Mix the carbon nitride described in step a with a 4 to 6 mol / L nitric acid solution, stir and react at 100 to 140 ° C for 16 to 28 hours, cool to room temperature, wash, separate the solid from the liquid, freeze-dry and grind the solid to obtain an intermediate; c. Mix the intermediate, polyacrylic acid and ionized water in step b, and ultrasonically treat for 15 to 30 min to obtain a dispersion, and hydrothermally react the dispersion at 160 to 240 ° C for 16 to 28 h to obtain a milky white dispersion; d. The milky white dispersion in step c is centrifuged at 7000-10000 rpm for 5-20 min to obtain a supernatant, and the supernatant is freeze-dried to obtain carbon nitride quantum dots with dual surface and core designs.

8. The method for preparing carbon nitride quantum dots with dual surface and core designs according to claim 7, characterized in that: The molar mass ratio of urea, diammonium hydrogen phosphate and boron trioxide in step a is 4:0.5-1.5:0.5-1.5; preferably 4:1:

1.

9. The method for preparing carbon nitride quantum dots with dual surface and core designs according to claim 7, characterized in that: The mass volume ratio of the intermediate and polyacrylic acid in step b is 1g:10-40mL; preferably 1g:20mL; the mass volume ratio of the carbon nitride and nitric acid solution in step b is preferably 1g:20-40mL.

10. The method for preparing carbon nitride quantum dots with dual surface and core designs according to claim 7, characterized in that: The hydrothermal reaction time in step c is 24 h.

Citation Information

Patent Citations

  • Preparation method of doped carbon nitride fluorescent quantum dots

    CN105670620A